Effects of Maintaining Social Distancing on Travel Intentions During Covid-19: Practical Implications to Tanzania’s Tourism Sector - Kara, Nasra (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
Although social distancing rule seem to be the effective measure to reduce the spread of the virus pandemic related diseases, the effectiveness of this rule varied country wise. The main focus of the current study was to analyze studies that have been done addressing relationship between social distancing and visitor’s travel intention during COVID-19 and to come up with a practical implication to Tanzania tourism sector. This was a desk review study and only full-length articles published in academic journals, mainly in tourism and hospitality were used. Data for this study was generated from three main tourism database search engines as EBSCOhost, science direct, and Google scholar using keywords such as “social distancing” “tourism” “COVID-19” “intention to travel” “hospitality”. The search retrieved a total of 7 articles. It was reported that perceptions of COVID-19 and the use of non-pharmaceutical intervention did not have an impact on behavioral intention. Individual desire was proved to have a positive effect on behavioral intention. Furthermore, the behavioral intention was negatively influenced by the affective risk and peoples’ emotions. During virus pandemic related diseases Tanzania need to emphasize on the use of technology and seat blocking strategy in transport sector to make sure that social distancing rule is fully maintained.